Does the presence of an epiretinal membrane alter the cleavage plane during internal limiting membrane peeling? - Kenawy, Nihal; Wong, David; Stappler, Theodore; Romano, Mario R; Das, Ronald A; Hebbar, Gillian; Prime, Wendy; Heimann, Heinrich; Gibran, Syed K; Sheridan, Carl M; Cheung, Yin Him; Hiscott, Paul S (Ophthalmology (Rochester, Minn.), 2010)
To determine whether the presence of a clinically and/or microscopically detectable epiretinal membrane (ERM) alters the cleavage plane during internal limiting membrane (ILM) peeling. Retrospective, observational, immunohistochemical study of ILM specimens using archival formalin-fixed, paraffin-embedded tissue. Fifty-one patients who had had ILM excision. Fifty-one ILM specimens peeled during vitrectomy for various etiologies were examined by light microscopy. The removal of ILM was assisted using Trypan blue (n = 30), indocyanine green (n = 7), or brilliant blue G (n = 14). Monoclonal antibodies to glial fibrillary acidic protein and to neurofilament protein were used to detect glial or neuronal cells respectively on the vitreous or retinal surfaces of the ILM. Specimens were divided into 2 groups: ILM peeled for full-thickness macular hole (MH; n = 31) and ILM peeled after removal of clinically detectable ERM (n = 20). Primary outcome measure was the localization of immunohistochemical markers to neuronal or glial cells on the vitreous or retinal surfaces of ILM. The secondary outcome measure was the correlation of the results of the primary measure with the dyes used to facilitate ILM peeling. Glial and/or neuronal cells were detected on the retinal surface of the ILM in 10 of 31 (32%) of the MH ILM specimens and in 13 of 20 (65%) of the ILM peeled after ERM excision; the difference was significant (P = 0.02). There was no association between the presence of neuronal and glial cells with the type of dye used (P = 0.2). Of the 23 ILM specimens with cells attached to the retinal surface, 21 (91%) were associated with clinical and/or histologic evidence of ERM and 2 (9%) were not. The correlation between the presence of cells on the vitreous and the retinal surfaces of ILM was high (P<0.0001). The findings suggest that ERM may be associated with sub-ILM changes that alter the plane of separation during ILM peeling. This study does not confirm any influence of dyes on the cleavage plane during surgery.